Consolidating diverse modeling methods and spatial prioritization for multispecies connectivity planning - Bohnett, Eve; Oetting, Jon; Noss, Reed; O’Brien, Michael; Frakes, Robert; Smith, Dan; Lockhart, Sarah; Mullinax, Jennifer; Poor, Erin E.; Scheick, Brian; Hoctor, Thomas (Frontiers in Conservation Science, 2024)
Introduction Given the different life histories and movement behaviors of diverse species, reconciling conservation measures to benefit all species is a critical concern for landscape conservation planning. Understanding land cover composition and finding multispecies movement routes across heterogeneous landscapes are crucial to maintaining many target species. The primary objectives of this study were to determine the optimal environment in Florida that promotes multispecies connectivity in landscapes increasingly threatened by rapid suburban development and to enhance methods for delineating the state’s ecological networks. Methods Potential functional connectivity of the focal species with statewide distributions and are considered priorities because of the historical and current threats to their population viability, such as the Florida black bear (Ursus americanus floridanus), Florida panther (Puma concolor coryi), eastern indigo snake (Drymarchon couperi), and southern fox squirrel (Sciurus niger niger), were modeled using Linkage Mapper, Omniscape, and resistant kernels. We combined quantiles from each method for a single species combination approach to leverage the results from the three models for planning purposes. Subsequently, we integrated the results into a novel multiple species, multi-model connectivity mapping approach. Following the corridor analysis, a comparison was made between multispecies connectivity maps, current managed conservation lands, and the main priority areas for the Florida Wildlife Corridor, a previously developed planning network of natural hubs and corridors. Finally, we used the spatial prioritization software Zonation to identify areas of conservation priority, while also illustrating the impacts of infrastructure (built infrastructure, roadways, mining, and future development 2040 and 2070 projections) and threats from human activity (landscape fragmentation, recreation, pollution, contamination, and clean-up sites). Results The study identified priority areas for all four species, with a particular focus on areas not currently protected. The connectivity models showed significant overlap with current managed conservation lands and the main priority areas for the Florida Wildlife Corridor. Pinchpoint areas or bottlenecks were identified as needing fine-scale incorporation into spatial planning. Using the spatial prioritization software Zonation, we identified areas of conservation priority and illustrated the impacts of infrastructure and threats. Discussion The results indicate that species-relevant connectivity models incorporating a group of focal species with both complementary and opposing habitat requirements can better inform biodiversity conservation and landscape design decisions. This multi-model approach provides a robust framework for identifying and prioritizing areas for conservation, particularly in landscapes facing rapid suburban development. Integrating multispecies connectivity models into conservation planning can enhance the effectiveness of ecological networks and contribute to the long-term viability of diverse species in Florida.